(untitled) (American Journal of Pedagogical and Educational Research, 2024)
Today, many business organizations including fast-food establishments are experiencing a decline in revenue as only a few are operating optimally, due to many external and internal factors, some of which have not been empirically validated. This, study, therefore, was an attempt to determine the effect of service design on brand loyalty in fast food organizations in Warri city, Delta State of Nigeria. The survey research design was adopted for the study whereby a sample size of 226 customers was drawn from the purposive sampling technique to generate primary data for the study through the questionnaire method. Simple percentage, mean score and standard deviations were deployed for descriptive and univariate analysis respectively while multiple regression was adopted for bivariate analysis involving hypotheses testing. The analyzed data revealed that innovativeness and technological resources had the most significant effect on repeat purchase in fast food organizations in Delta State of Nigeria, whereas context and target had positive but insignificant effect on repeat purchase. Based on the findings, it was concluded that all the dimensions of service design had varying degree of impact on brand loyalty in the fast-food organizations surveyed. Consequently, it was recommended that owners/managers of restaurants should embark on consumer research to determine target market preferences and those managers should redesign their menu to reflect customers’ profiles and dynamics and should uphold continuous products/service improvement through innovativeness with a view to exceeding visitors’ expectations for brand loyalty.